Local Cultural Heritage “Omo Hada” As An Icon Of Cultural Tourism Attraction In West Nias District - Kristina Octavia Sitompul; Yustina Denik Risyanti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Cultural heritage is one of the attractions of cultural tourism to attract tourists to visit a place. The local cultural landscape in the form of traditional houses and megalithic remains scattered across West Nias Regency is a special attraction for tourists. War strategies and local traditional rituals influenced the figure of Omo Hada. Buildings characterized by oval-shaped vernacular architecture are called in the local term "owulo". However, unfortunately, age and climate factors have made Omo Hada a building that has become obsolete over time. It was discovered that currently Omo Hada is threatened with extinction and has been contaminated by modern materials and supporting buildings. This research is basically to reveal the form and symbolic meaning and socio-cultural values ​​contained in the traditional house (Omo Hada) in West Nias Regency. This data collection was carried out by observation, documentation, interviews and literature study. Findings show that Omo Hada is no longer built by the community due to strict customary processes, and their numbers are also decreasing. West Nias Regency does not yet have traditional house names as its cultural identity, and there is no digital interpretation media for conservation. This discovery can provide recommendations to policy makers so that the name Omo Hada "Owulo" is patented as the name of the Traditional House of West Nias Regency. Cultural heritage needs to be equipped with interpretive media that is appropriate to current developments to preserve information and cultural heritage values.